SURVEI MULTI RESIDU ORGANOKLORIN DALAM BERAS DENGAN METODE GAS CHROMATOGRAHY ELECTRON CAPTURE DETECTOR (STUDI DI DISTRIBUTOR BERAS “X”SENTRA PENJUALAN BERAS DARGO KOTA SEMARANG) - Aritonang, Firman Apul; Saraswati, Lintang Dian; Udiyono, Ari (Jurnal Kesehatan Masyarakat (Undip), 2015)
Rice (Oryza sativa) is the world’s most important food crop and a primary source of food for most Indonesian people. Application of organochlorine pesticides in  rice and other factor cause pesticide residue contaminating rice. One of the most harmful pesticide residues that may contaminating rice is organochlorine pesticides. But in Indonesia, there is less information regarding the analysis of organochlorine pesticides residue in rice. The aims of this study were to analyse and  find organchlorine pesticides residue in rice. The research was conducted in Saraswanti Indo Genetech (SIG) pesticide residue laboratory. This observational analytic study using  gas chromatography electron capture detector (GC-ECD) method. The results show that organochlorine pesticide residue were not detected in rice. This study indicates the rice is safe for consumption according to Indonesian Goverment Legislation, SNI 7313:2008, and codex alimentarius pesticides residue in food.